2009
DOI: 10.1590/s0037-86822009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre os níveis plasmáticos de TNF-α, IFN-γ, IL-10, óxido nítrico e os isotipos de IgG específicos nas formas clínicas da doença de Chagas crônica

Abstract: Na década de 90, a doença de Chagas foi considerada pelo Banco Mundial como a doença parasitária mais importante na América Latina, com impacto socioeconômico consideravelmente maior do que os efeitos combinados de outras infecções parasitárias 6 . A doença, cujo agente etiológico é Trypanosoma cruzi, RESUMOA doença de Chagas é uma importante doença parasitária crônica, que acomete cerca de 9-11 milhões de pessoas na América Latina. Provavelmente, uma combinação de fatores relacionados ao parasito e ao hosped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
(13 reference statements)
0
7
1
1
Order By: Relevance
“…Our results differ from those reported by Ferreira et al [29] and Talvani et al [30]. However, a previous study from our group analyzing plasma TNF-alpha levels was unable to show differences between the clinical forms of chronic Chagas disease [33]. TNF-alpha plays a potential dual role, controlling parasite growth or promoting tissue damage.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from those reported by Ferreira et al [29] and Talvani et al [30]. However, a previous study from our group analyzing plasma TNF-alpha levels was unable to show differences between the clinical forms of chronic Chagas disease [33]. TNF-alpha plays a potential dual role, controlling parasite growth or promoting tissue damage.…”
Section: Discussioncontrasting
confidence: 99%
“…cruzi IgG 1 in Chagas patients. However, Pissetti, et al [ 29 ] showed that elevated levels of IL-10 correlated with elevated levels of total IgG 4 in the serum of patients with the digestive form of Chagas disease, indicating that IL-10 could contribute to total IgG 4 production in these patients. In fact, low production of anti- T .…”
Section: Discussionmentioning
confidence: 99%
“…This parasitic disease is caused by the protozoan Trypanosoma cruzi, transmitted by different routes: via the feces of infected triatomine bugs, contaminated blood transfusion, oral (contaminated food/juices), vertical transmission, organs transplantation and laboratory accidents. Approximately 60% of patients in the chronic phase are clinically asymptomatic, around 30% manifest cardiomyopathy, 8% megavisceral syndromes and the remaining 2% both cardiomyopathy and digestive involvement [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%